Gambaran Dampak Waktu Layar Terhadap Tidur Pada Remaja: Tinjauan Pelingkupan - Dianah, Haninan Salma; Sukaesih, Nunung Siti; Sejati, Amanda Puspanditaning (Jurnal Keperawatan Florence Nightingale, 2024)
Screen time is time spent watching television, using a laptop or computer, watching videos, playing games and using devices. In Indonesia, 62.5% of teenagers use social media for more than eight hours per day. Sleep is a basic human need or the main need in Abraham Maslow's hierarchical theory. The aim of this research is to determine the impact of screen time activities on teenagers. The method used was a systematic literature review. Articles were searched using the PubMed, Cochrane and Google Scholar databases. Articles were selected using the PRISMA flow diagram and the quality of the articles was analyzed using JBI (Joint Base Integrated). With eligibility criteria, namely 70% "Yes" score from all questions. Researchers use the boolean operators "AND" and "OR" in searching articles. As a result of the selection, there were 19 articles studied. The article was published in 2017-2023 with research locations in Saudi Arabia, China, India, Indonesia, Japan, Lebanon, Nepal, Pakistan, Taiwan and Turkey. All articles studied used a cross-sectional study design. The conclusion of this study is that screen time activities can have an impact on poor sleep quality, sleep disturbances, longer sleep latency and shorter sleep duration. Additionally, screen time can impact anxiety. stres, depression, overweight and low self-esteem.